«Silver volunteering» as a direction of social work with the elderly - Vakulenko, Svitlana (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2025)
The article considers «silver volunteering» as one of the relevant areas of social work. The author notes that in developed countries, social policy is structured in such a way as to stimulate the active participation of older people in public life, encouraging and supporting them, for example, through relevant programs within the framework of social work. Refusal to treat older people as objects of assistance and care, and instead involving them in the decision-making process that concerns both their personal lives and the lives of the community and society as a whole, are becoming increasingly common practices. The definition of «silver volunteering» is given as the voluntary and unpaid participation of older people in activities aimed at solving current social, cultural, economic, and environmental problems of society, for the implementation of which people apply their own knowledge, skills, and efforts. «Silver volunteering» can be considered from three positions: 1) as assistance from the state and non-profit organizations to older people; 2) as a mechanism for social adaptation; 3) as a means of overcoming persistent stereotypes about the elderly. In turn, volunteering of the elderly can be considered as one of the manifestations of active longevity. Currently, there are three main approaches to understanding active longevity. Within the framework of the first, active longevity is considered primarily as a continuation of the labor activity of citizens, therefore, in active longevity programs implemented in many developed countries, the economic aspect is taken into account first of all. Supporters of the second approach analyze both economic and social factors, in particular, they pay great attention to active leisure. The third approach emphasizes the need to maintain health at a certain level and ensure self-control and independence as a necessary condition for active longevity. Therefore, the introduction of «silver volunteering» and the development of relevant programs and projects will not only influence the involvement of older people in public life, but will also help preserve their health, self-confidence, increase self-esteem, and combat social isolation and loneliness.